Galectin-9 suppresses B cell receptor signaling and is regulated by I-branching of N-glycans - N. Giovannone (Nature Portfolio, 2018)
Leukocytes are coated with glycans that modulate immune function through interactions with lectins. Here, the authors characterize the N-glycan repertoire of human tonsillar B cells. They report that Gal-9 is an intrinsic regulator of B cell activation that may differentially modulate BCR signaling at steady state and within germinal centers due to expression of I-branched glycans.